Batu Cermin Cave Labuan Bajo Development Strategy Based on Tourist Satisfaction Level - Rudiyanto, Roseven; Iramadani, Bonifasia (Program Studi Hospitality dan Pariwisata, 2023)
Tourist satisfaction is essential for the sustainability of tourism activities at tourist attractions. Batu Cermin Cave is one of the attractions in Labuan Bajo. Batu Cermin Cave underwent renovations in 2021 and reopened in 2022. Since then, no studies have shown tourist satisfaction with the services and facilities at Batu Cermin Cave. Therefore, this research aims to determine the satisfaction level and develop strategies based on the level of tourist satisfaction. This research uses a mixed-method approach with an explanatory sequential design. Quantitative data collection uses accidental random sampling techniques with survey questionnaires and qualitative data uses observation techniques. The data collected came from 124 respondents. Data was analyzed using importance-performance analysis. In the Keep Good Work Quadrant, there were nine attributes: the appearance of the tour guide, speed of service of the tour guide or staff in serving visitors, the readiness of the tour guide or staff in serving visitors, timeliness of service, reliability in service, politeness and friendliness, patience in serving, area parking, and walking paths in the Batu Cermin Cave Area. In the Low Priority Quadrant, there are four attributes: work equipment for staff and tour guides in serving visitors, trash cans, information boards, and places to eat and drink. The Overkill Quadrant is an attribute of providing exceptional services for tourists and the road to Batu Cermin Cave. In the Top Priority quadrant, namely, security when visiting Batu Cermin, toilets, and road signs to Batu Cermin Cave. The priority development strategy is based on the attributes of the Top Priority quadrant are 1) increasing visitors' sense of security when carrying out tourism activities at Batu Cermin Cave, and 2) Improving the quality of supporting facilities such as toilets and road signs to Batu Cermin Cave..